Tren jenayah harta benda di Malaysia: kajian di Selangor dan Kuala Lumpur - Norita Jubit (Tanjong Malim, 2022)
Tren jenayah harta benda di Malaysia: kajian di Selangor dan Kuala Lumpur by Norita Jubit